Retrospective Evaluation of Colistin Associated Nephrotoxicity at Oncology Hospital Intensive Care Unit - Menşure Kaya; Yeliz İrem Tunçel; Rukiye Neslihan Kuru; Saadet Menteş; Süheyla Ünver; Sabahat Çeken; Mustafa Ertek (Galenos Yayinevi, 2014)
Objective: The aim of our study, is to determine the nephrotoxicity rates and risk factors for the development of nephrotoxicity by retrospective evaluation of patients who were given colistin therapy oncology hospital intensive care unit. Material and Method: Total of 33 adult patients were included in the study. Renal function tests and hemodialysis requirements were recorded. In addition, patients age, gender, concurrently used drugs with colistin therapy, duration of colistin therapy and total colistin doses were noted. RIFLE criteria (risk, injury, failure, loss, end-stage kidney disease) were used for evaluation of nephrotoxicity. Results: Nephrotoxicity was observed in 69,7% of patients (23 patients). According to RIFLE criteria nephrotoxicity rates were; risk 36,36%, injury 15,15% and failure 18,18%. In patients who developed nephrotoxicity, creatinine and blood urea nitrogen values were observed to rise significantly on the 5th day of colistin treatment (p≤0,05). In patients with malignancy, nephrotoxicity rate was 5.4 times higher than those without the diagnosis of malignancy. Concurrent use of diuretic, aminoglycoside, vancomycin and carbapenem did not increase the risk of nephrotoxicity. Conclusion: In our study, the rate of nephrotoxicity was higher than those in the literature. We found that underlying malignant tumor diagnosis increases the rate of nephrotoxicity.